ANALISIS JURNAL VARIASI GENETIK MAKHLUK HIDUP EUKARIOTIK - khairani, Miftahul; wardana purba, Balqis putri; umaroh, Izza yani; Nabilla, Mutiara; Rifda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The aim of this research is to analyze the differences between journals regarding the genetic variation of eukaryotic living creatures. This analysis was carried out on 10 journals, namely national journals and international journals. The research method used is kualitatif. The results of this research include national and international journals that match the researchers' criteria, namely journals with the keyword genetic variation and narrowed down further by discussing genetic variation in eukaryotic living creatures such as humans, animals and plants with a time span of years. The number of journals that will be analyzed in depth namely 10 journals with 6 national journals and 4 international journals.